2023
DOI: 10.1093/rheumatology/kead449
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with tixagevimab/cilgavimab is associated with lower COVID-19 incidence and severity in patients with autoimmune diseases

Marion Thomas,
Maeva Masson,
Samuel Bitoun
et al.

Abstract: Objective To describe the clinical efficacy of tixagevimab/cilgavimab in pre-exposure prophylaxis in patients at risk of severe COVID-19 and unresponsive to vaccination (anti-SARS-CoV-2 antibodies <260 BAU/mL) in rheumatology. Methods In this multicenter observational study we included patients with autoimmune or inflammatory diseases who received a pre-exposure prophylaxis by tixagevimab/cilgavimab between December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several studies have reported clinical data about different frail populations such as hematological malignancies, kidney and liver transplant recipients, patients with end-stage renal disease on chronic hemodialysis, autoimmune diseases, and other important comorbidities. Most of these studies observed that in populations unresponsive to vaccination, tixagevimab/cilgavimab pre-exposure prophylaxis was associated with lower incidence of COVID-19 and severe infection [ 15 , 16 , 17 , 18 , 19 ]. These clinical studies were conducted across various timeframes, resulting in patient exposure to diverse variants of concern (VOCs).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported clinical data about different frail populations such as hematological malignancies, kidney and liver transplant recipients, patients with end-stage renal disease on chronic hemodialysis, autoimmune diseases, and other important comorbidities. Most of these studies observed that in populations unresponsive to vaccination, tixagevimab/cilgavimab pre-exposure prophylaxis was associated with lower incidence of COVID-19 and severe infection [ 15 , 16 , 17 , 18 , 19 ]. These clinical studies were conducted across various timeframes, resulting in patient exposure to diverse variants of concern (VOCs).…”
Section: Discussionmentioning
confidence: 99%
“…After a median follow-up of 4.3 months, 23 COVID-19 cases were reported. The authors noted that the incidence of COVID-19 in this population was lower than the COVID-19 incidence in the general population during the study period, whereas patients who received an anamnestic injection had better protection against SARS-CoV-2 infection [ 56 ]. Another small study included patients with glomerular diseases who were under treatment with rituximab.…”
Section: Discussionmentioning
confidence: 99%